SISTEM INFORMASI MANAJEMEN KAS PADA KONVEKSI PUSTI BUSANA BERBASIS DESKTOP - Sudrajat, Ari; Cahyati, Imas; Putra, Candra Basroni (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2026)
Pusti Busana is a fashion business that previously managed cash receipts and payments manually, making it prone to recording errors and delayed financial reporting. This study aims to design and implement a desktop-based accounting information system for cash receipts and payments to support the company's operational activities. The system was developed using the Waterfall methodology, with data collected through observation, interviews, documentation, and literature review. System analysis was conducted using the PIECES framework, while process modeling employed Flowcharts and Data Flow Diagrams (DFD). The system was built using Visual Basic .NET as the programming language and MySQL as the database management system. Testing was carried out through Black Box Testing and User Acceptance Testing (UAT). Black Box Testing confirmed that all system functions performed as designed, while UAT yielded a score of 86%, indicating a very high level of user acceptance. The system produces cash receipt reports, cash expenditure reports, cash position reports, and cash transaction vouchers, enabling the owner to monitor the company's financial condition more efficiently and accurately.